Myelin Oligodendrocyte Glycoprotein (MOG) Optic Neuritis: A Case Series - Masnon Nurul-Ain; Zuhratun Nazihah Khairul Kamal; Wan-Hazabbah Wan Hitam; Maimunah Abdul Muna'aim; Faizah Mohd Zaki (Cureus, 2024)
Indexed by WOS/ERA